Experience with β-d-Glucan Assay for Diagnosis of Invasive Candidiasis in ICU Patients: Pilot Study from India. (4th October 2017) - Bansal, Nitin; Gopalakrishnan, Ram; Sethuraman, Nandini
Abstract: Background: β-d -Glucan assay (BDG) has been recently introduced in India and is recommended for the early diagnosis of invasive candidiasis (IC), but there are a number of factors (eg β-lactam antibiotics, immunoglobulin and albumin infusions, bacteremia and surgical mesh) which may falsely elevate BDG levels. Methods: This was a retrospective, observational study done in the 23 bedded multi-disciplinary ICU of a tertiary care hospital in South India. Case records of adult (> 18 years) non-neutropenic patients having severe sepsis or shock with ≥ 1 risk factor for IC were analyzed. As a standard practice, BDG assay was sent and effective antifungals were started on the day of suspicion of IC. All neutropenic, immunocompromised patients, those already on antifungal and those who were diagnosed with other invasive fungal infections were excluded from the study. FDA approved Fungitell assay was used to measure serum BDG levels (pg/mL). Results: Patients were divided into 3 groups. Group A ( n = 16) comprised of patients in whom diagnosis of IC was confirmed (blood culture or another sterile site grew candida). Group B ( n = 30) comprised of patients in whom alternative diagnosis of severe sepsis or septic shock was found or they did not improve after administration of antifungals. Group C ( n = 31) comprised of those patients in whom neither diagnosis of IC was confirmed nor an alternative explanation was found but they improved clinically on giving antifungal therapy. Mean BDG levels was significantly higher in Group A as compared with Group B and Group C (448.75 ± 88.30 vs 144.46 ± 82.49 vs 292.90 ± 137.0 pg/mL; P  < 0.001). The mean value of the BDG was higher than the accepted cutoff of 80 pg/mL in all three groups (Figure 1). The use of agents which cause false elevation of BDG was significantly higher in Group B as compared with Group A ( P  = 0.02). Conclusion: A BDG assay cutoff of 80 pg/mL leads to a higher number of false positive results in ICU patients, where false positive factors are unavoidable. The results of this study suggest that a higher cutoff of at least 144 pg/mL will be more specific for IC, although this may need further validation with larger trials. Disclosures: All authors: No reported disclosures.